(untitled) (Scientific journal of the Fergana State University, 2026)
The article studies the theoretical and methodological foundations of developing suggestive competence of future primary school teachers, the methodological system of developing suggestive competence of future primary school teachers, the effectiveness of developing suggestive competence of future primary school teachers. The pedagogical foundations of developing suggestive competence of future primary school teachers are also analyzed.